GC-MS profile of volatile compounds in Pogostemon Benghalensis (Burm.f.) kuntze and Pogostemon Cablin (Blanco) benth. - PRADEEP.D.P,; K.MURUGAN, (International Journal of Pharma and Bio Sciences, 2019)
Essential Oils (Eos) are unique natural volatile and odoriferous plant products. Eos are used in perfumery as well as in therapeutic industries. Essential oils play multiple roles such as defence, hormonal activities, initiate cellular regeneration, and work as protective against fungal, viral, and animal foes. Eos are composed of volatile compounds and these compounds mainly belongs to the group terpenoids and its derivatives. Pogostemon spp. belongs to the family Lamiaceae which are well known for a range of volatile constituents. But, most of them are underutilized. In this juncture, the present study is conducted to extract, identify and compare the essential oils of Pogostemon benghalensis (Burm.f.) Kuntze. and P. cablin (Blanco) Benth. The leaves of the Pogostemon cablin (Patchouli) are widely used for the large scale production of Patchouli oil, which is an important and unique commodity in the fragrance and medicinal industry. Fresh leaves of the plants were used for the isolation of essential oil. The leaves were subjected to steam distillation in a Clevenger type apparatus for the extracted of oil. The isolated oils were analysed by GC -FID followed by GC-MS. From analysing the chromatogram, 41 and 36 volatile compounds were identified from the leaf essential oil of P. benghalensis and P. cablin respectively. Patchouli alcohol and α-Cadinol were the major components in the oils oil of P. benghalensis and P. cablin respectively. These oils contained mainly sesquiterpene and oxygenated sequiterpene hydrocarbons. The difference in the quality and quantity of compounds present in the oils of selected Pogostemon species suggests their significant role in various therapeutic potentialities. Based on the qualitative and quantitative analysis, the oils from Pogostemon benghalensis and Pogostemon cablin can be used in perfumery industry and developed for the production of novel natural medicine.